Gut Microbiota and NAFLD: Pathogenetic Mechanisms, Microbiota Signatures, and Therapeutic Interventions - Tomas Hrncir; Lucia Hrncirova; Miloslav Kverka; Robert Hromadka; Vladimira Machova; Eva Trckova; Klara Kostovcikova; Pavlina Kralickova; Jan Krejsek; Helena Tlaskalova-Hogenova (Microorganisms, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. Its worldwide prevalence is rapidly increasing and is currently estimated at 24%. NAFLD is highly associated with many features of the metabolic syndrome, including obesity, insulin resistance, hyperlipidaemia, and hypertension. The pathogenesis of NAFLD is complex and not fully understood, but there is increasing evidence that the gut microbiota is strongly implicated in the development of NAFLD. In this review, we discuss the major factors that induce dysbiosis of the gut microbiota and disrupt intestinal permeability, as well as possible mechanisms leading to the development of NAFLD. We also discuss the most consistent NAFLD-associated gut microbiota signatures and immunological mechanisms involved in maintaining the gut barrier and liver tolerance to gut-derived factors. Gut-derived factors, including microbial, dietary, and host-derived factors involved in NAFLD pathogenesis, are discussed in detail. Finally, we review currently available diagnostic and prognostic methods, summarise latest knowledge on promising microbiota-based biomarkers, and discuss therapeutic strategies to manipulate the microbiota, including faecal microbiota transplantation, probiotics and prebiotics, deletions of individual strains with bacteriophages, and blocking the production of harmful metabolites.